Prevalence of Inhibitors in a Population of 3435 Hemophilia Patients in France - Sultan, Y; French Hemophilia Study Group (Thrombosis and Haemostasis, 1992)
A cooperative study between the 37 centers of the French Hemophilia Study Group was undertaken to establish the prevalence of inhibitor patients in the French hemophilia population. The prevalence reported in the literature varies widely from 3.6% to 17.5%. Some of the studies are dealing with a small number of patients and inhibitor patients are reported either to the total number of hemophiliacs or to the severely affected ones. The French study provided information concerning 3,435 hemophiliacs and showed a prevalence of 6.2% for the overall population. Prevalence of inhibitors was found to be 7% in the population of hemophilia A patients and 12.8% in the population of severely affected ones. The prevalence of inhibitors in the population of hemophilia B patients was 2% and 4% in the population of severely affected hemophilia B patients. The cooperative study also showed that 47.5% of inhibitors are detected before 10 years of age and that 82% of inhibitor patients are high responders. Analysis of inhibitor detection in patients under the age often showed that there was a peak in the population of 2 years old children. Although not comparable to the present study the high incidence of inhibitors with ultrapurified and recombinant FVIII reported in previously untransfused patient may be borne in mind.